Effective Use of Irrigation Water in Case of Interfirm Canal (Texas Journal of Engineering and Technology, 2022)
This article deals with the problems of large water losses in the “Ak-Yab” canal (Khorezm province, Uzbekistan) for filtration, as well as the factors that prevent this circumstance. At a time when the value of each drop of water is high and there is a shortage of water, the efficient use of irrigation canals to supply the water needed for crops is relevant. As a matter of this study, the assessment of the current state of the canal and the technical condition of the hydraulic structures in it was carried out using the observation methodology and long-term analysis of the collected data on this canal (in-situ). From a scientific point of view, specific proposals and conclusions were given for the repair and construction of the canal and its hydraulic structures. From a practical point of view, on the basis of data on the study of the state of the canal in the field, together with specialists in this field, the priorities for repair, rehabilitation and construction have been determined along the length of the Ak-Yab canal.